The surface chemistry determines the spatio–temporal interaction dynamics of quantum dots in atherosclerotic lesions. (March 2018) - Uhl, Bernd; Hirn, Stephanie; Mildner, Karina; Coletti, Raffaele; Massberg, Steffen; Reichel, Christoph A; Rehberg, Markus; Zeuschner, Dagmar; Krombach, Fritz
Aim: To optimize the design of nanoparticles for diagnosis or therapy of vascular diseases, it is mandatory to characterize the determinants of nano–bio interactions in vascular lesions.Materials & methods: Using ex vivo and in vivo microscopy, we analyzed the interactive behavior of quantum dots with different surface functionalizations in atherosclerotic lesions of ApoE-deficient mice.Results: We demonstrate that quantum dots with different surface functionalizations exhibit specific interactive behaviors with distinct molecular and cellular components of the injured vessel wall. Moreover, we show a role for fibrinogen in the regulation of the spatio–temporal interaction dynamics in atherosclerotic lesions.Conclusion: Our findings emphasize the relevance of surface chemistry-driven nano–bio interactions on the differential in vivo behavior of nanoparticles in diseased tissue.